From Classrooms to Careers: Foundational Insights on the Integration of Academic and Vocational Education and Training in Palestine - Salameh, Samer A. (Journal of Technical Education and Training, 2026)
Despite a growing number of university graduates, Palestine faces a severe unemployment crisis because the local labor market cannot absorb them all. At the same time, Vocational Education and Training (VET) remains underdeveloped and disconnected from actual market needs, leading to a significant skills gap. This paper explores how combining traditional academic education with vocational training could help solve Palestine’s unemployment problem. By reviewing existing data, economic theories, and successful international models from countries like Germany and Jordan, the study highlights the benefits of a blended educational approach. The findings clearly show that integrating academic and vocational learning equips students with better, more relevant skills, significantly improving their chances of finding good jobs. However, launching these programs in Palestine is difficult due to ongoing political and economic challenges, as well as a weak private sector that struggles to create new jobs. Ultimately, while blending these educational paths is not a magic cure, it is a crucial strategic shift. This approach can motivate young Palestinians, boost their competitiveness, and empower them to start their own businesses.